Trumbo Based on a Play by Christopher Trumbo - Trumbo, Christopher
"Trumbo" is a portrait of Oscar-winning screenwriter Dalton Trumbo, the wit and talent of whom is legendary. Forced into exile from Hollywood by Senator Joseph McCarthy's House Un-American Activities Committee, Trumbo continued to write by using several different pseudonyms, under which he produced some of his widely-acclaimed and award-winning screenplays. Letter-writing became the repository of Trumbo's extraordinary talents, and these correspondences serve as a wonderfully entertaining testament to the need for self-expression, social and political involvement, and remaining fallibly human in the face of barbarism. Told through performances of some of these extraordinary letters by an award-winning cast of actors archival and contemporary interviews and clips from his films, Trumbo illustrates how his unerring belief in the freedom of speech and the power of the written word allowed him to fight against political persecution. [Cover]
Keywords: DVD-Video